Evaluasi Penerapan Pencegahan Pasien Berisiko Jatuh di Rumah Sakit - Sanjaya, Puguh Danu; Rosa, Elsye Maria; Ulfa, Maria (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: Patient safety in hospitals is a service of a hospital system that provides care to enable patients to be more secure. Patient safety goals are to promote specific improvements in patient safety. The reduction in risk of patients falling aimed hospitals need to evaluate the risk of patient falls and take action to reduce the risk of injury when the fall is one of the goals of patient safety. This study reveals the evaluation of the application of preventive risk patient falls in Pupuk Kaltim hospital. Method: This study was a case study, in the inpatient room, the emergency room (ER) at the Pupuk Kaltim hospital. Results: This study resulted that the initial assessment in the emergency department (ED) has not been carried out, assessments of monitoring is not maximized, still found the beds are not safe as many as 26 pieces, grade three patients did not receive anti-slippery footwear. Policies and Standart Operational Procedure (SOP) has existed since 2013. Conclusion: The initial assessment of patients the risk of falling in the ER has not been carried out, assessments have not been up monitoring of risk patients, 26 beds are not safe, three unsafe gurney, patient grade three can not be footwear. Pupuk Kaltim hospital dissemination, evaluation and monitoring of the patient's fall risk assessment, infrastructure and facilities.